A comprehensive comparison of rail power conditioners based on two-level converters and a V/V power transformer in railway traction power systems - Tanta, Mohamed (2018)
Electric locomotives in the traction power systems represent huge nonlinear single phase loads and they affect adversely the public electrical grid stability and the power quality. Some of such problems are related to the harmonic distortion and the Negative Sequence Components (NSCs). The Rail Power Conditioners (RPCs) are widely used to accomplish harmonics mitigation, besides NSCs compensation, then, maintaining balanced and sinusoidal public electrical grid currents. This paper presents a comprehensive comparison study between three different RPCs based on the two level converters and a V/V power transformer. The Four Wire Rail Power Conditioner (FW RPC), the Three Wire Rail Power Conditioner (TW RPC) and the Half Bridge Rail Power Conditioner (HB RPC) are the main conditioners of interest. The main contribution of this paper is to perform a comprehensive comparison between the aforementioned RPCs, including the control algorithms and the compensating performance regarding the power quality problems. Simulation results with different operation scenarios are presented to establish an appropriate comparison between the aforementioned RPCs topologies.